Non-Cytotoxic Dibenzyl and Difluoroborate Curcuminoid Fluorophores Allow Visualization of Nucleus or Cytoplasm in Bioimaging - Obregón-Mendoza, Marco A. (Molecules, 2020)
Curcumin, the most important secondary metabolite isolated from Curcuma longa, is known for its numerous purported therapeutic properties and as a natural dye. Herein, based on curcumin’s intrinsic fluorescence, a search for improved curcumin-based fluorophores was conducted. Within the set of semi-synthetic curcumin derivatives i.e. mono (1), di (2), tri (3), tetra (4) benzylated and dibenzyl-fluoroborate (5), the fluorescence properties of 2 and 5 in solution outstood with a two-fold quantum yield compared to curcumin. Furthermore, all benzylated derivatives showed a favorable minimal cytotoxic activity upon screening at 25 μM against human cancer and non-tumoral COS-7 cell lines, with a reduction of its cytotoxic effect related to the degree of substitution. Fluorophores 2 and 5 are versatile bioimaging tools, as revealed by Confocal Fluorescence Microscopy (CFM), and showed permeation of living cell membranes of astrocytes and astrocytomas. When 2 is excited with a 405- (blue) or 543-nm (green) laser, it is possible to exclusively and intensively visualize the nucleus. However, the fluorescence emission fades as the laser wavelength moves towards the red region. In comparison, 5 allows selective visualization of cytoplasm when a 560-nm laser is used, showing emission in the NIR region, while it is possible to exclusively observe the nucleus at the blue region with a 405-nm laser.